Upper limb active prosthetic systems-overview - Castellini, Claudio (Wearable Robotics - Systems and Applications, 2019)
Active upper-limb prostheses are biocompatible mechatronic devices aimed at restoring, maybe partially but as satisfactorily as possible, the physiological functions lost after the amputation of an upper limb. In the past few decades, medicine, mechatronics, mathematics, and materials science have progressed together in the quest for the ideal upper limb active prosthesis. In this chapter we revise the state of the art and current limitations of this fascinating discipline, and outline a few directions for future research.
CRIS-Team Scopus Importer:2021-09-13
Keywords: Rehabilitation robotics; assistive robotics; human–robot interaction; intent detection; upper limb prosthetics